Research on main‐lobe deceptive jamming against FDA‐MIMO radar - Yingjian Zhao; Bo Tian; Chunyang Wang; Jian Gong; Ming Tan; Changlin Zhou (IET Radar, Sonar & Navigation, 2021)
Abstract A multiple‐input multiple‐output (MIMO) radar with frequency diverse array (FDA) produces a range‐angle‐dependent steering vector, which can suppress the deceptive jamming in joint range‐angle domain. This in turn complicates the task of radar jamming. With the emergence and development of digital radio frequency memory (DRFM), radar electronic jamming technique has entered the age of coherent jamming. Based on the analysis of the superiority of the FDA‐MIMO radar in cancelling the deceptive jammers, a novel range gate pull‐off method via DRFM against FDA‐MIMO radar is proposed. Compared with the traditional deceptive jamming methods, the proposed method cannot be suppressed due to the mismatch in range. In particular, even the anti‐jamming methods based on power domain cease to be effective. The effectiveness of the proposed scheme in jamming the tracking performance of the FDA‐MIMO radar is demonstrated via computer simulations.